CD43 expression is associated with inferior survival in the non‐germinal centre B‐cell subgroup of diffuse large B‐cell lymphoma. (25th April 2013) - Mitrovic, Zdravko; Iqbal, Javeed; Fu, Kai; Smith, Lynette M.; Bast, Martin; Greiner, Timothy C.; Aoun, Patricia; Armitage, James O.; Vose, Julie M.; Weisenburger, Dennis D.; Chan, Wing C.
Summary We evaluated the prognostic significance of CD43 (SPN), a membrane glycoprotein, in 140 patients with diffuse large B‐cell lymphoma (DLBCL) by tissue microarray (TMA) immunostaining, and gene expression profiling (GEP) in 43 patients. CD43 protein was expressed in 19% of the cases and was strongly related to the non‐germinal centre B‐cell (non‐GCB) subgroup by both TMA and GEP. Patients with CD43(+) DLBCL had an inferior 3‐year overall survival (OS) compared to those with CD43(‐) DLBCL (50% vs. 76%, P = 0·01). Within the non‐GCB subgroup, patients with CD43(+) DLBCL had a particularly poor 3‐year OS (32% vs. 71%, P < 0·001). Gene set enrichment analysis within the activated B‐cell subgroup revealed significant enrichment in the stromal‐1 signature in CD43(−) cases. We conclude that CD43 is an adverse prognostic marker in DLBCL, and is preferentially expressed in the non‐GCB subgroup. The dismal outcome of CD43(+) cases in the non‐GCB subgroup may be explained, at least in part, by a less favourable microenvironment.